2023
DOI: 10.3390/metabo13030327
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin Resistance as a Mediator of the Relationship between Body Weight, Waist Circumference, and Systolic Blood Pressure in a Pediatric Population

Abstract: Excess weight and high waist circumference (WC) are associated with increased blood pressure (BP), starting from the pediatric age. Insulin resistance is associated with elevated BP in childhood. The aim of the study was to assess the role of insulin resistance in mediating the relationship between body mass index (BMI), WC, and BP values in a pediatric population referred to a cardio-pediatric center for the presence of one or more cardiovascular risk factors. In 419 children (mean age 10.7 [standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, it is advisable to prevent obesity and other cardiometabolic comorbidities in individuals exposed to early undernutrition. It has previously been shown that in pediatric populations investigated for cardiovascular risk (elevated BP, excess weight or altered lipid profile), the HOMA-IR index is one of the most important factors associated with WC and SBP or other cardiovascular risk factors [ 51 ], even when body weight is not high enough to affect other obesity-related risk markers [ 52 , 53 ]. Accordingly, a correlation between abdominal perimeter and HOMA-IR was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is advisable to prevent obesity and other cardiometabolic comorbidities in individuals exposed to early undernutrition. It has previously been shown that in pediatric populations investigated for cardiovascular risk (elevated BP, excess weight or altered lipid profile), the HOMA-IR index is one of the most important factors associated with WC and SBP or other cardiovascular risk factors [ 51 ], even when body weight is not high enough to affect other obesity-related risk markers [ 52 , 53 ]. Accordingly, a correlation between abdominal perimeter and HOMA-IR was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that high insulin levels contribute to body fat accumulation, leading to an increase in BMI [ 18 ]. However, our study found that all RMS patients had hyperinsulinemia but were not obese, and some were even underweight.…”
Section: Discussionmentioning
confidence: 99%